2023
DOI: 10.1371/journal.pone.0285811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health care professionals’ knowledge, attitudes, practices and barriers to pharmacovigilance and adverse drug reaction reporting: A cross-sectional multicentral study

Abstract: Background Healthcare professionals’ involvement and reporting of adverse drug reactions are essential for the success of a pharmacovigilance program. The aim of this study was to assess healthcare professionals (medical doctors, pharmacists, nurses, dentists, midwives, and paramedics) current knowledge, attitude, practices, and barriers regarding pharmacovigilance and adverse drug reactions reporting in multicentral healthcare settings. Methods A cross-sectional face-to-face survey was conducted among curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Inferential statistical (chi-squared test) analysis was performed to assess the correlation between the demographic variables and KAP questions. The overall percent score cutoff was computed using the modified Bloom's cutoff point criteria, which had already been used in previous studies ( 24 , 25 ). We chose nine questions for the knowledge part, with each accurate response (yes:1) receiving one point and the incorrect response (no:0) receiving zero points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inferential statistical (chi-squared test) analysis was performed to assess the correlation between the demographic variables and KAP questions. The overall percent score cutoff was computed using the modified Bloom's cutoff point criteria, which had already been used in previous studies ( 24 , 25 ). We chose nine questions for the knowledge part, with each accurate response (yes:1) receiving one point and the incorrect response (no:0) receiving zero points.…”
Section: Methodsmentioning
confidence: 99%
“…The vaccinators were defined as having “good knowledge” if their score was above 75% (ranging from 77.7% to 100% with 7–8 points), “moderate knowledge” if their score ranged from 55% to 74% (5–6 points), and “poor knowledge” if their score was < 55% (< 5 points). The total practice score was categorized as “good practice” if it ranged from 75% to 100% (9–12 points) or “poor practice” if it was < 75% (8 points) ( 24 , 25 ). Logistic regression analysis was used to identify the differences in sociodemographic characteristics between training and non-training variables.…”
Section: Methodsmentioning
confidence: 99%
“…It is the science and practice of monitoring, detecting, assessing, and preventing adverse effects or any other drug-related problems associated with the use of pharmaceutical products. The primary objective of pharmacovigilance is to ensure the safe and effective use of medications by identifying and mitigating potential risks and promoting patient welfare [2]. Key components of pharmacovigilance include the collection and analysis of adverse drug reactions (ADRs) and other safety data from various sources such as healthcare professionals, patients, regulatory authorities, and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Doctors, chemists, nurses, and other paramedics have a huge responsibility to report ADRs and strengthen PV systems. However, low levels of reporting are associated with spontaneous ADR schemes [2]. A thorough assessment of European Union research indicated a substantial significant issue observed among healthcare professionals (HCPs) is the under-reporting of adverse drug reactions (ADRs), with a median rate of 94% under-reporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation